Estimulação adrenérgica causada pela administração de isoproterenol induz disfunção metabólica e remodelamento pancreático em ratos Wistar - Castro, Alessandra Gisele de (2022)
Isoproterenol is a drug commonly used for the treatment of bradycardia, heart block, bronchospasm during anesthesia and rarely for asthma. It is a non-selective β-adrenergic agonist analogue of epinephrine, for this reason it promotes positive inotropic and chronotropic effects in cardiac tissue, being used as an experimental model for the study of cardiac alterations. It is known that the adrenergic stimulation caused by the administration of isoproterenol induces cardiac remodeling, usually through pathways mainly related to redox status and inflammatory cytokines. However, little is known about the metabolic damage of this model. Thus, this study aims to evaluate the effects of isoproterenol administration on metabolic and morphological parameters. Adult Wistar rats (50-60 days old; weighing 200- 250g) were allocated into two experimental groups: control rats (CO) that received vehicle (150 mM NaCl, 0.1ml/kg/day; i.p.), and rats that received received injections of isoproterenol (ISO; 1 mg/kg/day; i.p.) for 7 consecutive days. After the treatment period, the animals were submitted to in vivo tests and later euthanized for sample collection. The animals in the ISO group did not show a significant difference in body mass compared to the CO animals. On the other hand, ISO animals showed increased brown adipose tissue mass and brown adipose area. Furthermore, the administration of isoproterenol promoted pancreatic remodeling, with an increase in the area of pancreatic islets and interstitial fibrosis. In short, in addition to cardiac changes, the adrenergic overload induced by isoproterenol administration was also able to promote significant morphological changes in brown adipose tissue and pancreas, these changes may be linked to changes in the heart and in other systems, thus, the study Integrated physiological training is fundamental for a better understanding of the exacerbated stimulation of β-adrenergic receptors.